Ergometer rowing with and without slides - Holsgaard-Larsen, A.; Jensen, K. (International Journal of Sports Medicine, 2010)
A rowing ergometer can be placed on a slide to imitate `on-water' rowing. The present study examines i) possible differences in biomechanical and physiological variables of ergometer rowing with and without slides and ii) potential consequences on training load during exercise. 7 elite oars-women rowed in a randomized order in a slide or stationary ergometer at 3 predefined submaximal and at maximal intensity. Oxygen uptake was measured and biomechanical variables of the rowing were calculated based upon handle force (force transducer) and velocity/length (potentiometer) of the stroke. Stroke frequency was higher (%-difference between conditions) at each intensity level (1-11.4%, p<0.05) during slide compared to stationary rowing. Furthermore, at the 2 highest intensities a lower mean force (4.7-9.0%, p<0.05) and max force (3.2-10.6%, p<0.05) were observed on the slide ergometer. During maximal rowing no difference was seen in heart rate, mean oxygen uptake and R-value while maximal oxygen deficit was higher (30.8%, p<0.05) during slide rowing. In conclusion the biomechanical load is lower on a slide than on a stationary ergometer. However, as a training tool the slide ergometer seems just as demanding with regard to aerobic energy sources, and for anaerobic sources possibly even higher, compared with the stationary ergometer.